Congenital bronchobiliary fistula: first case in an adult. Issue 10 (October 1988) - de Carvalho, C R; Barbas, C S; Guarnieri, R M; de Campos, J R; Filomeno, L T; Saldiva, P H; Barbas Filho, J V
Abstract : The first adult case of a congenital communication between the biliary tract and the right main bronchus is reported. Treatment by surgical excision and pneumonectomy was successful.